2014
DOI: 10.1007/s00586-014-3192-3
|View full text |Cite
|
Sign up to set email alerts
|

Can unilateral-approach minimally invasive transforaminal lumbar interbody fusion attain indirect contralateral decompression? A preliminary report of 66 MRI analysis

Abstract: Quantitative and qualitative parameters of the central canal and contralateral neural foramen increased significantly after unilateral-approach MITLIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Based on this concept, the minimally invasive treatment of DLSS is applied. Many scholars have reported that MISTLIF through bilateral decompression via unilateral approach has achieved good results in the treatment of DLSS [14][15][16]. OLIF is a minimally invasive anterior retroperitoneal approach surgery, which has been very popular in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this concept, the minimally invasive treatment of DLSS is applied. Many scholars have reported that MISTLIF through bilateral decompression via unilateral approach has achieved good results in the treatment of DLSS [14][15][16]. OLIF is a minimally invasive anterior retroperitoneal approach surgery, which has been very popular in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…11 Kim et al. 12 reported that unilateral MIS-TLIF can achieve indirect decompression of the contralateral foramen by increasing its height, width, and area. However, cases of contralateral radiculopathy following unilateral TLIF are still being reported.…”
Section: Discussionmentioning
confidence: 99%
“…Iwata et al [ 7 ] investigated the mechanism of this effect by detailed radiographic measurements on the contralateral intervertebral foramen (IVF); however, his study involved patients with spondylolisthesis and neglected the extra impact of intravertebral reduction on IVF morphology in the presence of spondylolisthesis. Similarly, Kim et al [ 8 ] documented that the morphological parameters of contralateral IVF increased significantly after unilateral TLIF and that these changes might contribute to indirect decompression on the contralateral side; however, this study overlooked the effects of different cage location within the intervertebral disc space (IVS).…”
Section: Introductionmentioning
confidence: 91%